WhatsApp as a Tool for Researching the Everyday Lives of Venezuelan Refugees Settling in Brazil - Amanda Alencar; Julia Camargo (Media and Communication, 2022)
In this article, we explore the role that WhatsApp can play as a research tool for investigating the experiences of settling refugees. Messaging apps can help researchers collect data about people’s everyday lives while also providing insights into processes that are difficult to study as they happen. The communicative affordances of messaging apps also facilitate spontaneous interactions in research and the flexibility needed when working with mobile groups of people, such as refugees. We build on our experience of interacting together with Venezuelan refugees through the Conexión Sin Fronteras (Connection Without Borders) WhatsApp group, which was designed by the researchers in the form of an intervention focused on building community among Venezuelans settling in the city of Boa Vista, Brazil. Our experience shows that data collection in WhatsApp allows researchers to obtain relevant insights into social support, relationship-building, and negotiations of rules in a group context. However, our research outlines challenges related to the varied engagement of participants in WhatsApp group chats and the difficulty for researchers to be always present during group conversations. Limitations to the use of WhatsApp in research with refugee populations also include restrictions in terms of internet capacity shaping the types of data participants choose to share. In this context, it is crucial to address barriers to access to connectivity and create opportunities to enhance refugees’ literacy regarding data collection in digital spaces. We hope these findings will contribute to the development of inclusive methodological approaches using mobile apps in refugee settings.